Additive Role of the Vestibular End Organ and Baroreceptors on the Regulation of Blood Pressure in Rats - Lan, Yan (The Korean Physiological Society and The Korean Society of Pharmacology, 2013)
Contribution of the vestibular end organ to regulation of arterial pressure was quantitatively compared with the role of baroreceptors in terms of baroreflex sensitivity and c-Fos protein expression in the rostral ventrolateral medulla (RVLM). Baroreflex sensitivity and c-Fos protein expression in the RVLM were measured in conscious rats that had undergone bilateral labyrinthectomy (BL) and/or baroreceptor unloading. BL attenuated baroreflex sensitivity during intravenous infusion of sodium nitroprusside (SNP), but did not significantly affect the sensitivity following infusion of phenylephrine (PE). Baroreflex sensitivity became positive following sinoaortic denervation (SAD) during infusion of PE and attenuated sensitivity during infusion of SNP. Baroreflex sensitivity also became positive following double ablation (BL+SAD) during infusion of PE, and attenuated sensitivity during infusion of SNP. c-Fos protein expression increased significantly in the RVLM in the sham group after SNP administration. However, the BL, SAD, and SAD+BL groups showed significant decreases in c-Fos protein expression compared with that in the sham group. The SAD group showed more reduced c-Fos protein expression than that in the BL group, and the SAD+BL group showed less expression than that in the SAD group. These results suggest that the vestibular system cooperates with baroreceptors to maintain arterial pressure during hypotension but that baroreceptors regulate arterial pressure during both hypotension and hypertension. Additionally, afferent signals for maintaining blood pressure from the vestibular end organs and the baroreceptors may be integrated in the RVLM.